Interactive Effects of Elevated CO2 Concentration and Light on the Picophytoplankton Synechococcus - Bao, Nanou; Gao, Kunshan (Frontiers in Marine Science, 2021)
Synechococcus is a major contributor to the primary production in tropic and subtropical oceans worldwide. Responses of this picophytoplankton to changing light and CO2 levels is of general concern to understand its ecophysiology in the context of ocean global changes. We grew Synechococcus sp. (WH7803), originally isolated from subtropic North Atlantic Ocean, under different PAR levels for about 15 generations and examined its growth, photochemical performance and the response of these parameters to elevated CO2 (1,000 μatm). The specific growth rate increased from 6 μmol m-2 s-1 to reach a maximum (0.547 ± 0.026) at 25 μmol m-2 s-1, and then became inhibited at PAR levels over 50 μmol m-2 s-1, with light use efficiency (α) and photoinhibition coefficient (β) being 0.093 and 0.002, respectively. When the cells were grown at ambient and elevated CO2 concentration (400 vs 1,000 μatm), the high-CO2 grown cells showed significantly enhanced rates of electron transport and quantum yield as well as significant increase in specific growth rate at the limiting and inhibiting PAR levels. While the electron transport rate significantly increased at the elevated CO2 concentration under all tested light levels, the specific growth did not exhibit significant changes under the optimal growth light condition. Our results indicate that Synechococcus WH7803 grew faster under the ocean acidification (OA) treatment induced by CO2 enrichment only under limiting and inhibiting light levels, indicating the interactive effects and implying that the picophytoplankton respond differentially at different depths while exposing changing light conditions.